Comparative Study Of Effect Of Alpha Glucosidase Inhibitors – Miglitol, Acarbose And Voglibose On Postprandial Hyperglycemia And Glycosylated Hemoglobin In Type-2 Diabetes Mellitus - DR. TELI SHAIKH EMARAN SHAIKH ISMAIL; DR. SARANG ANANTRAO DESHMUKH (International Journal of Pharma and Bio Sciences, 2012)
Diabetes mellitus has emerged as a major healthcare problem in India. Management of postprandial plasma glucose (PPG) level is important to prevent the complications associated with type-2 diabetes. Considering paucity of studies motivated us to compare the effect of Acarbose, Miglitol and Voglibose on postprandial hyperglycemia and HbA1C . It was single blind, randomized, parallel group, comparative, prospective clinical trial on 90 diabetes type 2 patients defined as post prandial plasma glucose (PPG) levels more than 200 mg % and glycosylated haemoglobin more than 7 % at visit 1. Glycosylated hemoglobin (p=0.78) and post prandial blood glucose (p=0.61) was reduced more by Voglibose than Miglitol and Acarbose. Though this finding is not statistically significant, adverse effect profile was better with Voglibose (6.66%) than Miglitol (16.66%) and Acarbose(33.33%). Present study recommends use of Voglibose looking at its efficacy and safety profile as preferential choice in the management of postprandial hyperglycaemia in treatment of type-2 diabetes mellitus.